The Effect of Media Use of Comics Without Text and Direct Learning on Narrative Writing Skills for Grade IV Elementary School Student - Syahrul R; Darnis Arief; Maryani Maryani (Postgraduate School, Universitas Negeri Padang, 2019)
This study aims to reveal the Effect of Media Use of Comics Without Text and Direct Learning on Narrative Writing Skills for Grade IV Elementary School Students. The type of research used is Quasi Experiment in the form of Randomized Control Group Only Design. The population in this study were fourth grade students of SDN Gugus V District X Koto Tanah Datar District with a sample of fourth grade students at SDN 26 Singgalang and fourth grade students at SDN 30 Singgalang. Sampling is done by Simple Random Sampling technique. The technique of analyzing data through initial knowledge tests, and the final test of narrative writing skills. The hypothesis is proposed using the t test formula. The results of the study showed that there was an effect of media use of comics without text and direct learning on narrative writing skills of grade IV elementary school students with narrative writing skills tests of students learning using comic media without text higher than students learning using direct learning with an average in the experimental class 83.37 and the average in the control class was 76.75.